Island biogeography of tropical alpine floras. (9th October 2013) - Sklenář, Petr; Hedberg, Inga; Cleef, Antoine M.; Gillman, Len N.
Abstract Aim We analysed the effects of alpine area, geographical distance between mountains and isolation due to topography on mountain plant species richness, regional species turnover and patterns of species distribution. Location Equatorial mountains of East Africa, South America and New Guinea. Methods We collated lists of alpine species and estimated the extent of alpine area for seven mountains in each geographical region to construct species–area curves. We tested the observed frequency distribution of species among mountains against the expected distribution (assuming random dispersal) by means of a log‐likelihood test. We compared species turnover among mountains using species accumulation curves. We expressed floristic similarity between mountain pairs as chi‐square distance between observed and expected numbers of shared species and tested its correlation with geographical distance using the Mantel test. Results Samples of East African, South American and New Guinean alpine floras contained 371, 489 and 279 species, respectively. Andean genera tended to be more species rich than genera in the other regions. Species richness of the mountains correlated with log‐transformed area except in East Africa. Species distributions among mountains significantly deviated from random in all regions. Species turnover was lowest among East African sites and highest among South American sites, and the slopes of the cumulative species–area relationship were significantly different. Floristic similarity between mountains significantly declined with log(distance) in all regions, and the slope of the relationship was steepest in South America. Main conclusions The flora of the Andean páramo is confirmed to be the most species rich of the tropical alpine regions. Páramo genera tend to be richer in species than afroalpine and tropicalpine Asian genera. There is higher species turnover in the Andes and the floras of individual mountains are therefore quite distinct. In contrast, the floras of the East African mountains are more uniform and possess a relatively large number of widespread species.